2018
DOI: 10.1002/sim.8043
|View full text |Cite
|
Sign up to set email alerts
|

A correlated Bayesian rank likelihood approach to multiple ROC curves for endometriosis

Abstract: In analysis of diagnostic data with multiple tests, it is often the case that these tests are correlated. Modeling the correlation explicitly not only produces valid inference results but also enables borrowing of information. Motivated by the Physician Reliability Study (PRS) that investigated the diagnostic performance of physicians in diagnosing endometriosis, we construct a correlated modeling framework to estimate ROC curves and the associated area under the curves.This correlated approach is quite appeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This is illustrated by a recent Cochrane review, suggesting using tests sequentially, beginning with the test with the highest sensitivity, and then re-testing the negative group ( Nisenblat et al 2016 ). Although the added value of a second test and the combined accuracy of tests can be calculated with a Bayesian approach ( Broemeling, 2011 ) as illustrated recently for endometriosis ( Chen and Hwang, 2019 ; Chen et al, 2019 ), this is still rarely used.…”
Section: Methodsmentioning
confidence: 99%
“…This is illustrated by a recent Cochrane review, suggesting using tests sequentially, beginning with the test with the highest sensitivity, and then re-testing the negative group ( Nisenblat et al 2016 ). Although the added value of a second test and the combined accuracy of tests can be calculated with a Bayesian approach ( Broemeling, 2011 ) as illustrated recently for endometriosis ( Chen and Hwang, 2019 ; Chen et al, 2019 ), this is still rarely used.…”
Section: Methodsmentioning
confidence: 99%
“…The difficulty was illustrated in a recent Cochrane review, suggesting to use tests sequentially, using first a test with high sensitivity, and subsequently using another test to re-test the negative group (24). The added value and the combined accuracy of tests can be calculated with a Bayesian approach as demonstrated for endometriosis (25,26), but this is overall rarely used.…”
Section: Clinical Considerations Of Traditional Analysis Of Treatment...mentioning
confidence: 99%
“…Literature was reviewed which claimed to be using Bayesian approaches but were not centred on the concept of casual Bayesian Network models. Correlated modelling framework to estimate ROC curves and the associated area under the curves was applied to the diagnostic performance of physicians in their diagnosing of endometriosis which suggested that clinical information may play a more important role in physicians' diagnostic performance than their experiences (Chen, et al, 2019). Endometriosis phenotypes were learned from patient-generated data through unsupervised learning (Urteaga, et al, 2020).…”
Section: Endometriosis and Machine Learningmentioning
confidence: 99%
“…Endometriosis is a relatively common and potentially debilitating gynaecological disorder that affects 6-10% of women of reproductive age (Rogers, et al, 2013). It is present in about a quarter of women who are infertile (Chen, et al, 2019). Endometriosis is a long-term condition defined as the presence of endometrial-like tissue outside the uterus and it is associated with a chronic and inflammatory reaction.…”
Section: Introductionmentioning
confidence: 99%